An Analysis of Physics Learning Motivation Using a Case Study-Based Learning Motivation Assessment Instrument - Setiaji, Bayu; Wiyatmo, Yusman; Diyana, Tsania Nur; Pujianto, Pujianto; Gustama, Malik Wira; Vidaroini, Saadah; Solehati, Cahyaningrum; Sakinata, Asya Maulida; Febriani, Febriani; Bunma, Chancira (Jurnal Inovasi Pendidikan IPA, 2024)
Learning motivation is important to support successful learning. This article discusses the analysis of high school learning motivation and the development of a learning motivation assessment instrument. This is due to the lack of instrument development based on case studies. It used a case study-based instrument developed with the 4D model. The study results show that the developed learning motivation assessment instrument is valid and reliable. Through this instrument, students' motivation to learn physics can be classified into low, medium, and high. Through analysis, the treatment of each group can be seen so that learning motivation can increase. At the low level, it can be increased by varying learning models, learning resources, and learning media. While for the second level, namely the average, it needs to be increased again by building more intense communication with students. For the highest level, it can be in the form of learning with more interesting learning resources and physics assignments.